Leguminous vegetables are harbinger for tribals - Gangadhara, K; Yadav, Lalu Prasad; Apparao, V V; Singh, Sanjay; Saroj, P L (Indian Horticulture, 2019)
The leguminous vegetables, viz. Indian bean, cluster bean and cowpea, have potential to fight the problems of protein and minerals in malnutrition affected tribal areas. Therefore, documentation of traditional crop knowledge and dissemination of information relating to the indigenous plant food utilization is very essential for solving nutritional problems. Apart from this, these beans forms excellent forage and they give a heavy vegetative growth and covers the ground so well that it checks the soil erosion. As a leguminous crop, they fix atmospheric nitrogen and boosts crop health. Introducing the above mentioned advanced agronomic practices would bring tremendous increase in yields and will ultimately improve the socioeconomical conditions of tribal people.